HIGH CONCENTRATION PREFERENTIAL ADSORPTION OF ZINC ACETATE ONTO ACID TREATED ACTIVATED CARBON FOR IMPREGNATION PURPOSES - Farooq, A.; Mehboob, S.; Chaudhary, M. M.; Irfan, N. (The Nucleus, 2020)
Impregnation of activated carbon has long been the subject of researchers working in the area of protection against air pollutants, especially those interested in making personal protective equipments. People who are involved in research of heavy metal removal using activated carbon have worked at very low concentrations. Moreover, the literature available in the open domain does not reveal the secrets of working at high concentration i.e., greater than 1 mM. Working at higher salt concentrations is necessary for the purpose of impregnating the activated carbon to a certain level with metals like copper, zinc, silver, chromium, tungsten, molybdenum etc. Activated carbon impregnated with these metals can be very effective in the removal of certain toxic gases. A locally available microporous activated carbon GAC89 was pretreated with nitric acid. B.E.T. surface areas and Boehm titrations were done. A large range of concentrations of aqueous solution of zinc acetate which is a preferentially adsorbing salt was made and stirred with the raw AC and the pretreated AC. Atomic absorption spectroscopy was employed to determine the amount of zinc acetate actually adsorbed onto the carbon sample. The results were fitted to a sum of two distinct adsorption isotherms, one for low concentrations i.e., less than 1 mM, and the other for high concentrations. The lower concentration adsorption is largely influenced by the solution pH. It is observed that at higher concentrations, the adsorption is weaker and the underlying mechanism is under study.